(untitled) (Revista LIDER, 2020)
The following article is based on a qualitative research concerning Initial Teacher Training (ITT) in Chile. A concise historic overview of the process is presented, to later center on the ITT actual scenario. The work analyzes institutions, students, curricular reforms, evaluation criteria of teacher performance, and the requirements which are necessary to become a teacher in Chile.